2017
DOI: 10.18844/prosoc.v3i5.1954
|View full text |Cite
|
Sign up to set email alerts
|

Pattern design preference based on symmetry

Abstract: Repetition is one of the design principles employed to create decorative pattern on several products such as textiles, wallpaper, ceramic tiles and gift wraps. In this study costumer preference of pattern used in decorative textile design is investigated. It is believed that this will be useful for designers and merchandisers who need to analyze public preference for textiles products. However, symmetry is a fundamental aspect of pattern design, design grouping and classification of designs used in research st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…Also, Friedenberg (2018) demonstrated that standard deviations of side lengths and types of symmetry have an influence on observers' aesthetic judgment of polygons. Meanwhile, aesthetic judgments can also be influenced by symmetrical transformations and symmetry groups of tiles (Friedenberg, 2019b;Sanad, 2017).…”
Section: The Influence Of Regularitymentioning
confidence: 99%
“…Also, Friedenberg (2018) demonstrated that standard deviations of side lengths and types of symmetry have an influence on observers' aesthetic judgment of polygons. Meanwhile, aesthetic judgments can also be influenced by symmetrical transformations and symmetry groups of tiles (Friedenberg, 2019b;Sanad, 2017).…”
Section: The Influence Of Regularitymentioning
confidence: 99%